2009
DOI: 10.1111/j.1753-0237.2009.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Aviation fuel demand modelling in OECD and developing countries: impacts of fuel efficiency

Abstract: On the quest for reducing the fuel consumption per passenger per flight for economical and environmental reasons, commercial aircraft manufacturers are implementing new strategies for optimising aircraft performance by using new lighter and stronger materials and enhancing engines' efficiencies in terms of fuel consumption and maintenance requirements. With the rising and falling of economies, whether in the Organization for Economic Cooperation and Development (OECD) countries or other developing countries, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…For the latter, there are few credible estimates in the literature due to endogeneity concerns, as airlines can react to changing prices by, for example, altering the number of seats on their aircraft, thereby influencing prices. However, a review of the literature suggests that jet fuel demand is quite price inelastic, with correlational estimates ranging between 0.04 and 0.30 (Mazraati and Alyousif, 2009).…”
Section: H Price Elasticity Of Fuel Demandmentioning
confidence: 99%
“…For the latter, there are few credible estimates in the literature due to endogeneity concerns, as airlines can react to changing prices by, for example, altering the number of seats on their aircraft, thereby influencing prices. However, a review of the literature suggests that jet fuel demand is quite price inelastic, with correlational estimates ranging between 0.04 and 0.30 (Mazraati and Alyousif, 2009).…”
Section: H Price Elasticity Of Fuel Demandmentioning
confidence: 99%
“…All these measure were for reducing fuel consumption. Mazraati and Alyousif [50] explained the effect of jet fuel prices, airline ticket prices on the fuel consumption and travel demand. Joosung J. Lee [31] suggested the social pressure and public awareness for fuel burn and emission reduction.…”
Section: Socio-economic and Politicalmentioning
confidence: 99%
“…Mohammad [1] concluded that the importance of the energy and economic markets will continue in the future, and predicted that the US and China markets would grow rapidly. Lee and Fahey [2] found that air traffic had been growing by 5.3% per year on average, based on year 2000 operational data.…”
Section: ⅱLiterature Reviewmentioning
confidence: 99%